SISTEM INFORMASI PEMESANAN MAKANAN DAN MINUMAN BERBASIS WEBSITE (STUDI KASUS : KOPI DALU) - Amalia Dwi Handayani (2023)
This booking information system is an information system that will be applied in Coffee Dalu which is located in the Ciputat area, City of Tangerang South. Seeing the process of service and ordering on Coffee Dalu is still long enough to cause a long run, then the writer with the coffee Dalu team work together to build an information system that is easy to use and more effective in estimating the time used in serving its customers. In the manufacture of this system uses the PIECES method. Design and development of the system using the waterfall method. The waterfall method includes user needs, analysis, design, implementation and testing. Modeling built using the object-oriented method UML (Unified Modeling Language). The system also uses the CodeIgniter 3 Framework with Black Box Texting testing. The programming language used is PHP with a MySQL database.